Penyuluhan Bahaya Narkoba Di Kalangan Remaja Khususnya Pelajar SMKN 1 Kisaran - Suriani Suriani; Chairanda Al Azmi; Muhammad Aldi Prayuda Sitorus; Chandra Ridho Wijaya; Lili Kahirina Azhari Lubi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
The purpose of this community service activity is to educate students at SMK Negeri 1 Kisaran on how to avoid drug abuse. drug abuse. This community service activity used an counseling strategy; all activities were planned and conducted with 25 student representatives from each grade and level. The comparison results between pre-test and post-test showed that the PKM can improve the knowledge of participants about the dangers of drugs and drug abuse prevention efforts; the number of participants who were able to mention the types of drugs, the dangers of drugs, and efforts to prevent drug drug abuse prevention efforts increased from 30% to 95%, and the average score reached 87 out of the maximum score. reached 87 out of the maximum score.